Spermidine Is Critical for Growth, Development, Environmental Adaptation, and Virulence in Fusarium graminearum - Tang, Guangfei; Xia, Haoxue; Liang, Jingting; Ma, Zhonghua; Liu, Wende (Frontiers in Microbiology, 2021)
Putrescine, spermidine and spermine are the most common natural polyamines. Polyamines are ubiquitous organic cations of low molecular weight and have been well characterized for cell function and development process of organism. However, the physiological functions of polyamines remain largely obscure in plant pathogenic fungi. Fusarium graminearum causes Fusarium head blight (FHB) and leads to devastating yield losses and quality reduction by producing various kinds of mycotoxins. Herein, we genetically analyzed the gene function of polyamine biosynthesis pathway and evaluated the role of the endogenous polyamines in growth, development and virulence of F. graminearum. Our results found that deletion of spermidine biosynthesis gene FgSPE3 caused serious growth defective, reduced asexual and sexual reproduction, and got more sensitive to various stresses. More importantly, ΔFgspe3 exhibited a significant decreased mycotoxin deoxynivalenol (DON) production and weak virulence in host plant. Additionally, the growth and virulence defects of ΔFgspe3 could be rescued by exogenous application of 5 mM spermidine. Furthermore, RNA-seq displayed that FgSpe3 participated in many essential biological pathways including DNA, RNA and ribosome synthetic process. To our knowledge, these results indicate that spermidine is essential for growth, development, DON production and virulence in Fusarium species, which provides a potential target to control FHB.